Exploring the Interaction of Tartrazine and Lipase: A Multispectroscopic Analysis, Docking and Computational Simulation Methods - Liu, Baosheng; Zhang, Hongcai; Cheng, Xu (Asian Journal of Pharmaceutical Research and Development, 2019)
The interaction between food colorant tartrazine and lipase was studied by multi-spectroscopic and molecular docking simulation under simulated physiological conditions to evaluate the toxic of tartrazine at the protein level. The results showed that tartrazine could effectively quench the endogenous fluorescence of lipase. The thermodynamic parameters were obtained from the van't Hoff equation, and the Gibbs free energy ΔG<0, indicating that the reaction was spontaneous; ΔH<0, ΔS>0, indicating hydrophobic interaction played a major role in forming the tartrazine-lipase complex. as shown by the synchronous fluorescence, UV-vis absorption and circular dichroism data, tartrazine could lead to the conformational and micro environmental changes of lipase, which may affect its physiological function. Molecular docking results showed that tartrazine was site in the active center of lipase, which altered the microenvironment of amino acid residues at the catalytic active center of lipase.